The Waste Arising as An Effect of The Opening of River Tubing Tourism Place, Mayangsari City, Semarang - Fajar, Fajar; Setyowati, Dewi Liesnoor; Juhadi, Juhadi; Putri, Noviani Achmad; Nurpratiwiningsih, Laelia (E-Journal of Tourism; Volume 10 Number 2 (September 2023), 2023)
Tourism objects besides providing benefits to managers and the surrounding community, also bring new problems, one of which is the waste problem. This article aims to analyze the waste problem at the new Mayangsari River tubing tourist attraction, Semarang City, and find out the forms of waste management at the Mayangsari River tubing tourist attraction, Semarang City. This study uses a descriptive qualitative research method. This research is located in Kalipancur Village, Ngaliyan District, Semarang City. The data in this study were collected through data collection techniques in the form of interviews, observation, and documentation. The informants in this study were taken from the management of the Tourism Awareness Group (Pokdarwis), the management of the Family Disaster Preparedness (KSB), the management of the River Care Community (KSP), the Rukun Warga and Rukun Tetangga groups, as well as the community, especially those who open businesses in these tourist areas. Data were analyzed using Miles and Huberman's interactive analysis model. The opening of the Mayangsari river tubing tour has resulted in an increase in the amount of waste generation. The increase in the amount of waste occurs on holidays in line with the high number of visitors. Every week about half of the contents of the garbage pickup is waste generated from tourist sites. The most common type of waste is plastic from food scraps. Trash is still found dumped around the river. Garbage is mixed even though organic and non-organic trash bins have been provided by the manager. Waste management through the application of 3 R (reduce, reuse, and recycle) has not been carried out by the management of this tourist spot. The waste generated from this tourist location is only limited to being collected then transported and then disposed of.